Selection of Weaning and Adult Weight to Increase Growth of Deutch Democratic Yokohama (DDY) Mice - Meireni Cahyowati; Endang Baliarti; Sumadi Sumadi (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This study aims to determine the increase of the growth of Deutch Democratic Yokohama (DDY) strain mice through a selection program from generation 0 (G0, n = 323 ), generation 1 (G1, n = 367) to generation 2 (G2, n = 386). The variables used for the selected program were weaning weight (WW) and adult weight (AW). For WW, the selection was made on the best 50% WW, and for the AW, the selection was carried out by choosing the best eight males and the best 32 females, using the value of genetic parameters and breeding values. Based on the study, WW increased from G0 to G1 and G1 to G2 of 12,63% and 12,05%, respectively. The increase in AW from G0 to G1 and G1 to G2 was 7,85 % and 17,78%, respectively. The conclusion was that it was possible to increase weaning weight and adult weight by selecting the program.